Open Versus Laparoscopic Repair of Perforated Peptic Ulcer Disease: A Propensity-matched Study of the National Emergency Laparotomy Audit. Issue 5 (12th May 2022) - Coe, Peter O.; Lee, Matthew J.; Boyd-Carson, Hannah; Lockwood, Sonia; Saha, Arin
Abstract : Objective: The aim of this study was to compare open surgery (OS) with laparoscopic surgery (LS) for perforated peptic ulcer (PPU) disease using a National dataset. Background: PPU disease is typically treated surgically with an omental patch. This can be performed through OS or a LS. Current evidence in OS versus LS suggests equivalence in mortality and postoperative complications, but a decrease in pain and wound infections with LS. Methods: A one-to-one propensity score-matched analysis of patients who underwent PPU repair from December 2013 to December 2017 using data from the National Emergency Laparotomy Audit was performed. Patients with an initially laparoscopic approach were classed as LS even if converted to OS. The primary end-point was 90-day mortality; secondary endpoints were length of stay (LOS), re-operation, and re-admission to critical care. Multivariable logistic and linear models were created to compare the effect of operative approach on binary and continuous outcomes with log-rank tests for time-to-event data. Results: A total of 5253 patients underwent surgery in the study period. After propensity-matching, 2 groups of 1158 patients were created. Overall 90-day mortality was 7.5%. There was no difference between the LA and OA for 90-day mortality (7.2% vs 8.5%, OR 0.80, 95% CI 0.56– 1.15, P = 0.23), median LOS (equivalent at 7 days, P = 0.09), reoperation (3.6% vs 4.0%, P = 0.74), or re-admission to critical care (2.8% vs 2.9%, P = 0.92). Across the 4-year study period LS use increased from 20% to 26% and the conversion rate decreased from 40% to 31%. Conclusions: Short outcomes from laparoscopic PPU repair appear equivalent to open repair. There is increasing adoption of LS with decreasing conversion rates. LS for PPU appears to be an acceptable approach in this setting.